Integration site features of proviruses from Acute UD, Acute UD + 5 and Chronic UD individuals. (A) Pie charts displaying proportions of IS in genic regions with same, opposite and mixed orientation relative to the host gene. (B) Pie charts displaying proportions of IS in centromeric/satellite DNA, ZNF genes with KRAB domain on chr19, other genic regions and other non-genic regions. (C) Bar plots showing the proportions of IS in Hi-C compartments A1-A2 and B1-B4. Cumulative proportions of IS in compartments A and B are indicated on the left side of the graph. (D) Bar plots showing the proportions of IS in repetitive elements. Cumulative proportions of IS in repetitive elements are indicated on the left side of the graph. (E-F) Boxplots showing ChIP-Seq reads corresponding to activating (E) or inhibiting (F) histone features in linear proximity (+/-5 kb) of IS. (A-D) n represent the number of IS in the analysis. Chi-squared test (A) or Fisher’s exact test (B- - Tine Struyve (22683295) (2025)
Integration site features of proviruses from Acute UD, Acute UD + 5 and Chronic UD individuals. (A) Pie charts displaying proportions of IS in genic regions with same, opposite and mixed orientation relative to the host gene. (B) Pie charts displaying proportions of IS in centromeric/satellite DNA, ZNF genes with KRAB domain on chr19, other genic regions and other non-genic regions. (C) Bar plots showing the proportions of IS in Hi-C compartments A1-A2 and B1-B4. Cumulative proportions of IS in compartments A and B are indicated on the left side of the graph. (D) Bar plots showing the proportions of IS in repetitive elements. Cumulative proportions of IS in repetitive elements are indicated on the left side of the graph. (E-F) Boxplots showing ChIP-Seq reads corresponding to activating (E) or inhibiting (F) histone features in linear proximity (+/-5 kb) of IS. (A-D) n represent the number of IS in the analysis. Chi-squared test (A) or Fisher’s exact test (B-